KATA GANTI ORANG DALAM BAHASA INGGRIS DAN BAHASA TIDORE SUATU ANALISIS KONTRASTIF - Djafar, Ansar (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This Skripsi entitled â€œThe Personal Pronouns In English and Tidore Language; A Contrastive Analysisâ€. The objectives of the research are to identify, analyze and describe personal pronouns in both languages based on the form, function and meaning and then to find out the similarities and dissimilarities according to Lado (1957) and Whitman (1970) concepts. There are two theories used in this research, namely, Bloomfield (1933) and Arts and Arts (1982). The data in English were collected from several linguistic books whereas the data of Tidore languge were collected from informants as primer data and the secunder data were collected from internets. English is a member of Germanic language family that is direct descendant of Indo-European and that consists of fifty-three languages. It is a member of Indo-European languages while Tidore language is the North Halmaheran of West Papuan phylum, classification language family found only in eastern Indonesian (West Papuan and North Halmahera) it is non-Astronesian. The result of this research indicates that personal pronouns in English and Tidore language Consist of first, second and third persons. There are some similarities and differences in both personal pronouns. The similarities of personal pronouns in both languages are in third person and second person. However, forms of second person in Tidore language have varieties. The main difference of both languages can be seen in first person. Tidore language distinguished several forms of personal pronouns based on cultural system such as age, economic abilites, social identity and relationship while English does not. Key words Personal pronouns, English and Tidore Language, Contrastive Analysis